An Improvement Intended For Multiple Crack Diagnosis Adopting Combo Artificial Intelligence Technique - Nanda, Jajneswar; Das, Layatitdev; R. Parhi, D (International Journal of Engineering and Technology, 2018)
Abstract: In the existing article, an innovative combination technique has been efficiently implemented to properly recognize the specific position and intensity of the transverse surface crack in a fixed-fixed shaft. The rod is suitably fixed on two modest bearings at bothÂ ends includingÂ axial and twisting loadÂ for the fixed angular arrangement in the longitudinal direction. The fluctuation parametric measure so as expected frequencies, mode shapesÂ are interrogatedÂ in theÂ proximity of two crack depths (bi) with their specific locations (Li) using stress intensity factor. Stress intensity factor is typically an objective function of compliance matrices. It is estimated as implementing one desired end of the shaft as the fixed bearings with the considerable help of an analytical method. The identical shaft is designed precisely to accurately determine the vibration signatures at respective vicinity using correctly an experimental procedure.A developed methodology MANFIS-GAÂ (an inverse technique)Â is implemented correctly to identify the proper position andÂ intensityÂ of possible crack from any one of the direct bearing.Â ComplexÂ MANFISÂ system consists precisely of four composedÂ ANFISÂ layer.Â The possible input to everyÂ ANFISÂ step is adequately equipped with the first three fundamental frequencies along with their modal values.Â The standard output of the activeÂ ANFISÂ part prognosticates the interim crack positions and desired depths.Â The interimÂ outputsÂ from fourÂ ANFISÂ (MANFIS)Â are carefully taken as the specific inputs to the automated G.A. system.Â The outputs from the modernÂ G.A.Â system are invariably final crack locations along with crack depths.Â TheÂ potencyÂ of the satisfactory MANFIS-GA results is authenticated byÂ correlatingÂ theÂ resultsÂ with the experimental setup.Â By reasonably interpreting the possible outcomes, it is presumed that this recommended methodology is valid for online and time saving for fault analysis of the cracked structure.Â Â